Closer to nature: the role of MSCs in recreating the microenvironment of the hematopoietic stem cell niche in vitro - Wuchter, Patrick; Diehlmann, Anke; Klüter, Harald (Transfusion medicine and hemotherapy, 2022)
Background: The stem cell niche in human bone marrow provides scaffolds, cellular frameworks and essential soluble cues to support the stemness of hematopoietic stem and progenitor cells (HSPCs). To decipher this complex structure and the corresponding cellular interactions, a number of in vitro model systems have been developed. The cellular microenvironment is of key importance, and mesenchymal stromal cells (MSCs) represent one of the major cellular determinants of the niche. Regulation of the self-renewal and differentiation of HSPCs requires not only direct cellular contact and adhesion molecules, but also various cytokines and chemokines. The C-X-C chemokine receptor type 4/stromal cell-derived factor 1 axis plays a pivotal role in stem cell mobilization and homing. As we have learned in recent years, to realistically simulate the physiological in vivo situation, advanced model systems should be based on niche cells arranged in a three-dimensional (3D) structure. By providing a dynamic rather than static setup, microbioreactor systems offer a number of advantages. In addition, the role of low oxygen tension in the niche microenvironment and its impact on hematopoietic stem cells need to be taken into account and are discussed in this review. Summary: This review focuses on the role of MSCs as a part of the bone marrow niche, the interplay between MSCs and HSPCs and the most important regulatory factors that need to be considered when engineering artificial hematopoietic stem cell niche systems. Conclusion: Advanced 3D model systems using MSCs as niche cells and applying microbioreactor-based technology are capable of simulating the natural properties of the bone marrow niche more closely than ever before.
Online veröffentlicht: 14. Januar 2022
Gesehen am 13.08.2024